Treatment Patterns of Follicular Lymphoma in the United States: A Claims Analysis - Scott F. Huntington; Sreevalsa Appukkuttan; Wenyi Wang; Yuxian Du; Sari Hopson; Svetlana Babajanyan (Journal of Health Economics and Outcomes Research)
**Background:** A consensus is lacking on optimal treatment sequencing for follicular lymphoma (FL), the most common indolent lymphoma. FL is incurable, and many patients require multiple lines of therapy for successive relapses. Guidelines provide numerous recommendations for first-, second-, and third-line therapy; however, treatment patterns in the real world remain poorly understood.